"The Impact of the Corona Epidemic on the lessee ’s Obligations in the Lease Contract" - Bani-Meqdad, Mohammad Ali Mohammad (International Journal of Membrane Science and Technology, 2023)
This study aimed to find legal solutions to the effects of the lease contract, especially the obligations of the lessee, with an indication of the impact of the Corona epidemic on the breach of these contractual obligations in the lease contract. The descriptive analytical approach was used, so the legal texts regulating the lease contract were analysed , and the consequent obligations thereof , explaining what the jurists and commentators went to in light of the exceptional circumstances. The research showed that the Corona epidemic has caused great and unusual damage to the world, whether material or physical.